PENGARUH MATA KULIAH MANAJEMEN KEWIRAUSAHAAN DAN LINGKUNGAN KELUARGA TERHADAP MINAT BERWIRAUSAHA MAHASISWA SEKOLAH TINGGI ILMU EKONOMI INDRAGIRI (STIE-I) RENGAT - Dewi, Kurnia; Yulianda, Airine; Yaspita, Hasanah (LPPM Press STIE Indragiri Rengat, 2019)
This research is at Economic Colleges of Indragiri Rengat with a quantitative approach. This research used primary data that the author obtained from respondents who are students of the Economic Colleges of Indragiri Rengat. This research used descriptive research, explaining that descriptive research is the largest form of research shown to describe the events that exist. The characteristics of the descriptive method are: 1) Focusing on the problems that exist in the present and the current period and 2) The data collected is first arranged, explained and analyzed. To anyzed the data, this research used multiple regression, correlation coefficients, and hypothesis testing which will be assisted using SPSS version 21. The results of Multiple Linear Regression Analysis in this study indicate that the value is significant. For the variable entrepreneurship interest has a significant influence on the subject of entrepreneurship management. Furthermore, family environment variables have a significant influence on entrepreneurship management courses. Partial test results (T-test) obtained the value of entrepreneurial interest variable with a large tcount from ttable, based on the data testing criteria it can be seen that H0 is rejected and Ha is accepted, it means that entrepreneurship partially influences the entrepreneurship management course and the value of the family environment variable with a large tcount from the table, based on the data testing criteria it can be seen that H0 is rejected and Ha is accepted, it means that the family environment partially influences the entrepreneurship management course. The results of the R test test, the value of r or correlation has a very strong and unidirectional relationship between the variables of entrepreneurial interest and variables family environment increases, the entrepreneurship management course will also increase and the value of r square or coefficient of determination has the meaning that the variable entrepreneurship management can be explained by variables of entrepreneurial interest and family environment variables, as while the rest is explained by other independent variables not examined in this research.